(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
The rapid development of science and technology makes mathematics very important. Because the development of science and technology can not be separated from the role of mathematics. It is almost certain that every part of science and technology both in general studies, pure and applied sciences requires the role of mathematics as a science of his assistance. Mathematics is used as an important tool in various fields, including natural sciences, engineering, medicine / medical, social sciences such as economics, and psychology. The newest branch of mathematics related to Computer science that is quite well known is the graph theory offered about graphs. In mathematics, graph is the basic object of learning. Graphs are often used to represent objects and are given with other objects. In everyday life humans cannot be released from the application of mathematics. Mathematics becomes the main thing to answer various challenges in the future. Indonesia ranks 45th out of 140 countries regarding country competitiveness in terms of infrastructure, adaptation technology, business economic difficulties, health, skills and innovation. This proves that mathematics is needed in the development of Indonesia because it is the basis of many aspects of life.